KEPATUHAN HUKUM NOTARIS/PPAT KOTA MEDAN TERHADAP PEMENUHAN KEWAJIBAN SEBAGAI PENGUSAHA KENA PAJAK - KIMUN KUARA (PREMISE LAW JURNAL, 2014)
ABSTRACT According to the Law on Value-Added Tax, the entrepreneurs who give the taxable goods/services are required to report their businesses in the process of registering themselves as Taxable Entrepreneurs, then they are also required to meet the tax obligations as Taxable Entrepreneurs. Therefore, a Notary/Land Certificate Issuing Officer is responsible to meet the stipulation of the Taxable Entrepreneurs registration except under the circumstances that the Notary/Land Certificate Issuing Officer belongs to Small Scale Entrepreneur. In fact, a regulation is frequently not obeyed by the public including the Notary/Land Certificate Issuing Officer community in Medan, due to several constraints. The result of this study showed that the compliance rate of the Notaries/Land Certificate Issuing Officers in Medan, in terms of their obligation to register themselves as Taxable Entrepreneurs was still low. The most main factor that made the Notaries/Land Certificate Issuing Officers in Medan disobey the regulation was that they had not understood the registration provisions. The effectiveness of the provisions on the registration of Taxable Entrepreneurs in the Notaries/Land Certificate Issuing Officers in Medan is still low and requires constant supervision of the tax authorities. Keywords : Compliance, Notaries/Land Certificate Issuing Officers, Registration, Taxable Entrepreneurs